Poaching the News Producers: The Athletic's Effect on Sports in Hometown Newspapers. (17th August 2020) - Buzzelli, Nicholas R.; Gentile, Patrick; Billings, Andrew C.; Sadri, Sean R.
ABSTRACT: When The Athletic, a conglomerate of subscription-based sports sites, launched in 2016, both its business model and editorial stance were viewed as a seismic shift in the journalism industry. Built on the notion that readers would eagerly pay a monthly fee to have access to the type of in-depth, customized coverage that print outlets often failed to deliver, The Athletic garnered a reputation for poaching newspapers' top sports talent with perceived job security and greater flexibility in terms of writing style. This zero-sum game approach has caused a disruption to the traditional rendering of culture and localized societal community within sports media. Therefore, to determine the type of impact that The Athletic's presence in hometown media markets has on local newspapers, 22 semi-structured in-depth interviews were conducted with sports editors and producers. The results illustrate that The Athletic presents competition on three fronts: one for top writing talent, one for content differentiation, and yet another for share of a market space flooded with other outlets. However, most interviewees agreed that the strongest form of direct competition is not for engaged readers, but rather for the most recognizable reporters in a given market.